Chest pain in lupus patients: the emergency department experience. Issue 11 (November 2015) - Modi, Masoom; Ishimori, Mariko; Sandhu, Vaneet; Wallace, Daniel; Weisman, Michael
Abstract Heart disease, a major cause of morbidity and mortality in SLE patients, often manifests as chest pain (CP). Our goal was to understand the prevalence and outcome of CP presentations for SLE patients in the emergency department (ED). Billing records of patients who presented to Cedars-Sinai Medical Center ED with ICD-9 codes for SLE and secondary ICD-9 codes for CP (786.50–786.59) between March 2009 and October 2013 were reviewed. Two study groups were formed: discharge from ED versus hospital admission. Visits were evaluated for basic cardiac work-up with an electrocardiogram (EKG) and cardiac enzymes; hospital admissions were evaluated for CP etiology and discharge diagnoses. Of 2675 ED visits with ICD-9 codes for SLE, 397 visits had secondary codes for CP (15 %); 173 were discharged and 224 became hospital admissions. While 92 % of admissions had basic cardiac work-up, over 50 % had chest pain attributed to non-cardiac causes. Only 7.2 % had a discharge diagnosis related to cardiovascular disease. Fifteen percent of all SLE coded patients had complaints of CP, a figure higher than the national average for non-SLE CP (10 %). There is a majority of non-cardiac diagnoses given to SLE patients at discharge. CP is likely to be a window of opportunity to address the known cardiac morbidity and mortality in SLE patients perhaps at an early stage of development of this complication. Our study strengthens the need for more investigations to assess the etiology of CP in this population.